Three Taxa in One: Cryptic Diversity in the Black Fly Simulium nobile (Diptera: Simuliidae) in Southeast Asia - Van Lun Low; Hiroyuki Takaoka; Pairot Pramual; Peter H. Adler; Zubaidah Ya’cob; Chee Dhang Chen; Subagyo Yotopranoto; Adnan Zaid; Upik Kesumawati Had; Maria Lourdes T Lardizabal; Affan Nasruddin-Roshidi; Mohd Sofian-Azirun (Oxford University Press, 2016)
We access the molecular diversity of the black fly Simulium nobile De Mejiere, using the universal cytochrome c oxidase subunit I (COI) barcoding gene, across its distributional range in Southeast Asia. Our phylogenetic analyses recovered three well-supported mitochondrial lineages of S. nobile , suggesting the presence of cryptic species. Lineage A is composed of a population from Sabah, East Malaysia (Borneo); lineage B represents the type population from Java, Indonesia; and lineage C includes populations from the mainland of Southeast Asia (Peninsular Malaysia and Thailand). The genetic variation of lineage C on the mainland is greater than that of lineages A and B on the islands of Borneo and Java. Our study highlights the value of a molecular approach in assessing species status of simuliids in geographically distinct regions.